Assessing Assessments: Substance use disorder treatment providers' perceptions of intake assessments. Issue 1 (1st December 2022) - Padwa, Howard; Treiman, Katherine; Mark, Tami L.; Tzeng, Janice; Gilbert, Marylou
Abstract: Background: Assessments to determine patients' treatment needs and preferences when they begin substance use disorder (SUD) treatment are essential. The objectives of this paper are to identify the perspectives of providers who conduct assessments on (1) assessments' utility in determining the level of care where patients will receive treatment, (2) strategies to engage patients in treatment during assessments, and (3) assessment strengths and shortcomings. Methods: Semi-structured interviews were conducted with 30 California treatment providers who routinely perform SUD assessments for Medicaid beneficiaries. Interviews asked about the utility of assessment tools in determining appropriate levels of care, patient engagement during assessments, and strengths and shortcomings of intake assessment processes. Interviews were audio-recorded, transcribed, and analyzed by multiple researchers using template analysis. Results: Providers reported that assessments linked to level-of-care decision rules sometimes generate recommendations inconsistent with their clinical judgment, and that the timing of assessments can influence the quality of the information collected. Providers described engagement strategies that help patients feel more comfortable during assessments and that encourage more thoughtful and accurate responses. Providers valued assessments that helped ensure comprehensive collection of patient information, that allowed flexibility to probe for additional information and context, and that facilitated treatment planning. Providers did not like assessments that were long and repetitive or those that did not collect detailed information about patients' mental health and recovery environments. Conclusions: Assessments can be improved if providers conduct them in a manner that makes patients feel comfortable while building trust and rapport. Ensuring that assessments are not long or repetitive and giving comprehensive assessments once patients have developed trusting relationships with treatment programs can improve assessment processes. Further research is needed to optimize SUD assessments.